Surgical ampullectomy: an underestimated operation in the era of endoscopy - Schneider, Lutz; Contin, Pietro; Fritz, Stefan; Strobel, Oliver; Büchler, Markus W.; Hackert, Thilo (HPB, 2016)
Benign neoplastic, inflammatory or functional pathologies of the ampulla of Vater are mainly treated by primary endoscopic interventions. Consequently, transduodenal surgical ampullectomy (TSA) has been abandoned in many centres, although it represents an important tool not only after unsuccessful endoscopic treatment. The aim of the study was to analyse TSA for benign lesions of the ampulla of Vater.
Available online 16 December 2015
Gesehen am 19.05.2020